Fauna de Coleoptera Lamellicornia en las montañas del noreste de Hidalgo, Mexico - Angel Morón, Miguel (Instituto de Ecología, A.C., 1994)
A comparative analysis of the scarab beetle fauna of the humid mountains of Zacualtipán, Molango, Atezca, Otongo and Tlanchinol, NE Hidalgo, México is presented. Data were obtained during 1975- 1981 with 1,360 days of collecting effort in pine forest, oak forest, cloud forest, tropical rain forest, induced pasture land and secondary vegetation, between 630-2100 m. Records of 12 subfamilies, 27 subtribes, 68 genera and 180 species are presented. The greatest specific diversity corresponds to Melolonthinae (40 spp,), Rutelinae (32 spp.), Scarabaeinae (29 spp.), Dynastinae (28 spp.) and Aphodinae (1 8 spp.). About 50 % of the specific diversity is concentrated m nine genera: Phyllophaga (24 spp.l. Anómala (12 spp.), Cyclocephala (9 spp.), Diplotaxis (8 spp.), Euphoria (8 spp.), Onthophagus (8 spp ), Aphodius (8 spp.), Plusiotis (7 spp.) and Ataenius (7 spp.]. Phyllophaga ravida. Ph. obsoleta, Polyphylla hammondi, Plusiotis adelaida, Chrysma rnacropus. Anómala aff. meonstans, Cyclocephala jalapensis, C. lurida, Strategus aloeus, Deltochilum gibbosum, Onthophagus cyanellus, Odontotaenius zodiacos and Heliscus tropicus were the rnost abundant species in the samples, The moniane scarab beetle fauna of Hidalgo shows 35 % of specific similarity and 65 % of genenc similarity with The area of Los Tuxilas Biológical Station, Veracruz, and represen! 12.3 % of the Lamellicornian species recordad in México. Nine endemic species are considered as endangered: Plesiosternus seiosus, Plusiofis terroni. P. taylori, P. aurofoveata. Orizabus endrodianus, Peltotrichius linea, Cotinis onenrahs, Spurius halfften and Olieus nonstriatus. A key to the taxa found in these mountains is included.